2020
DOI: 10.1016/j.jclinepi.2020.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Title, abstract, and keyword searching resulted in poor recovery of articles in systematic reviews of epidemiologic practice

Abstract: Objective: Article full texts are often inaccessible via the standard search engines of biomedical literature, such as PubMed and Embase, which are commonly used for systematic reviews. Excluding the full-text bodies from a literature search may result in a small or selective subset of articles being included in the review because of the limited information that is available in only title, abstract, and keywords. This article describes a comparison of search strategies based on a systematic literature review o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 10 publications
1
16
0
Order By: Relevance
“…Thirdly, our search may not have revealed all relevant literature. A recent study [41] found that many articles that use a particular methodology do not report its use in the title or abstract. Consequently, our review could have missed relevant articles which use propensity score methods.…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, our search may not have revealed all relevant literature. A recent study [41] found that many articles that use a particular methodology do not report its use in the title or abstract. Consequently, our review could have missed relevant articles which use propensity score methods.…”
Section: Discussionmentioning
confidence: 99%
“…The first relates to the different literature content contained within the different databases; this is not a new observation (Pautasso, 2014), but it does potentially impact significantly on the outcomes of database searches (Moral-Muñoz et al ., 2020). Further, the use of keyword searches of title, abstract and keywords listed in publications has its limitations; it was recently reported that the content of a publication is not always accurately reflected in the title or abstract (Penning de Vries et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Existing reviews either examine IVs in general [9,10,16,39,40] or are narrative PP IV reviews [41]. Here we contribute to the literature on PP IV through a systematic review focused on PP IV applications using a search strategy involving fulltext mining [42], using databases that enable complete article text searches. We present novel data on applications, including academic and clinical areas, reporting of IV assumptions, potential bias from selection on treatment and strength of various PP IV definitions.…”
Section: 2mentioning
confidence: 99%